Acoustic emission in compressed Mg-Li and Al alloys processed by ECAP, HPT and ARB methods - Pawełek, Andrzej; Piątkowski, Andrzej; Kuśnierz, Jan; Bogucka, Joanna; Jasieński, Zdzisław; Ranachowski, Zbigniew; Ranachowski, Przemysław; Mizera, Jarosław; Kúdela, Stanislav; Kúdela Jr., Stanislaw (Archives of Acoustics, 2007)
In the paper there are presented the results of investigations of the relations between acousticemission (AE) and the plastic strain mechanisms during channel-die compression of materials,based on both Mg-Li and Al alloys, having ultra fine-grained (UFG) or nanocrystallinestructure obtained using the technique of equal channel (of both quadratic and circular section)angular pressing (ECAP) as well as the technique of high pressure torsion (HPT). Alsothe AE in compression and tensile tests of UFG (nanocrystalline) Al alloys obtained by accumulativeroll-bonding (ARB) method have been investigated. The results obtained using anew generation AE analyzer are compared with those obtained for similar materials but notsubjected to ECAP, HPT and ARB processing. Moreover, the wavelet analysis of the detectedAE signals based on the acoustic maps (acoustograms) and spectral characteristics has beencarried out and the AE behaviour is discussed in the dislocation aspects of both plastic strainmechanisms and possible superplastic flow in UFG or nanocrystalline materials.